Do pension funds reach for yield? Evidence from a new database - Maximilian Konradt (Graduate Institute of International and Development Studies, 2023)
This paper investigates the financial risk-taking behavior of pension funds since 2000. I assemble a new database containing portfolio holdings of more than 100 pension funds from 14 advanced economies. The study reveals three key findings. First, I show that pension fund portfolios have become riskier over that period, with an average increase in risky asset weights of 4 percentage points since 2008. European pension funds tend to invest more in public equities, while North American and Asian funds focus on alternative assets. Second, I find evidence that declining domestic risk-free rates play a significant role in driving the trend, with pension funds increasing their risky asset exposure in response to falling short-term interest rates. Third, I demonstrate that less underfunded pension funds with fewer risky assets tend to reach for yield more aggressively, which is exacerbated during periods of low risk-free rates. This is most pronounced for European pension funds, particularly after the global financial crisis.
Keywords: E43; F21; G11; G23; 330; Low interest rates; Pension funds; Risk-taking; Reach for yield